Analysis of the Content of the Social Studies Book for the Sixth Elementary Grade in Light of the Priority of the Kingdom of Saudi Arabia’s Position and Pioneering Role (The International Journal of Educational Sciences and Arts, 2024)
The research aims to examine the degree of inclusion of the Priority of the Kingdom of Saudi Arabia’s Position and Pioneering Role in the content of the Social Studies Book for the Sixth Elementary Grade. To achieve this goal, the two researchers prepared an analyzing tool of (4) main dimensions comprising (56) indicators for the Priority of the Kingdom’s Position and Pioneering Role. To confirm the tool’s validity, it was presented to a number of specialist arbitrators. The calculation of the tool’s reliability was made by analyzing the material itself two times, on two remote periods. The first researcher’s analysis results were compared with the results of the second researcher using Holsiti’s equation for such a calculation. The value of the mean reliability coefficient was (0.99) and the analysis results indicated that the book included (28) sub-indicators for the priority of the Kingdom’s Position and Pioneering Role representing 50% with differing inclusion percentages. The indicator which reads (the content is ardent to boast the cultural heritage, and the Saudi and Arabic and Islamic history) scored the highest inclusion percentage which was 23%, followed by the indicator which reads (the content develops positive attitudes towards tolerance, coexistence, and acceptance of cultural diversity) scoring (15%). Some indicators have no existence such as the indicator which reads (the content shows the importance of the two holy mosques and their Islamic position).
Keywords: Content Analysis; Social Studies; Elementary Stage; Position of the Kingdom of Saudi Arabia